Those Who Can't Sort, Steal: Caste, Occupational Mobility, and Rent-Seeking in Rural India - Nicholas Lawson; Dean Spears (Institute of Labor Economics (IZA), 2019)
Three important features of Indian labor markets enduringly coexist: rent-seeking, occupational immobility, and caste. These facts are puzzling, given theories that predict static, equilibrium social inequality without conflict. Our model explains these facts as an equilibrium outcome. Some people switch caste-associated occupations for an easier source of rents, rather than for productivity. This undermines trust between castes and shuts down occupational mobility, which further encourages rent-seeking due to an inability of workers to sort into occupations. We motivate our contribution with novel stylized facts exploiting a unique survey question on casteism in India, which we show is associated with rent-seeking.
Keywords: O15; J71; J24; J47; 330; caste; occupational mobility; rent-seeking; India; labour markets in developing countries